2020
DOI: 10.3390/ijms21186686
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sirtuins in Kidney Diseases

Abstract: Sirtuins (SIRTs) are class III histone deacetylases (HDACs) that play important roles in aging and a wide range of cellular functions. Sirtuins are crucial to numerous biological processes, including proliferation, DNA repair, mitochondrial energy homeostasis, and antioxidant activity. Mammals have seven different sirtuins, SIRT1–7, and the diverse biological functions of each sirtuin are due to differences in subcellular localization, expression profiles, and cellular substrates. In this review, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 152 publications
(173 reference statements)
2
35
0
Order By: Relevance
“…Each sirtuin plays a different role and has variable expression levels in various tissues and cells with different substrates and their own subcellular distribution. Due to the ability to target post-translational acyl modifications of various cellular substrates, sirtuins are crucial to numerous biological processes including proliferation, DNA repair, mitochondrial energy homeostasis, and antioxidant activity [88].…”
Section: Fibrosis In Dkdmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sirtuin plays a different role and has variable expression levels in various tissues and cells with different substrates and their own subcellular distribution. Due to the ability to target post-translational acyl modifications of various cellular substrates, sirtuins are crucial to numerous biological processes including proliferation, DNA repair, mitochondrial energy homeostasis, and antioxidant activity [88].…”
Section: Fibrosis In Dkdmentioning
confidence: 99%
“…Recent research has demonstrated a role for SIRT1 in proximal tubule-podocyte communication in association with the SGLT2. In the diabetic kidney, HG levels within the proximal tubules will trigger glucose transporter 2 (GLUT2)-mediated intracellular glucose uptake via SGLT2 upregulation, causing an associated decrease in SIRT1 [88].…”
Section: Role Of Sirtuins In Dkdmentioning
confidence: 99%
“…SIRT1, a mammalian ortholog highly closed to Sir2, belongs to the Sirtuins family (SIRT1-SIRT7) whose function depends on nicotinamide adenine dinucleotide (NAD+) and is highly conserved in evolution (Hong et al, 2020 ). SIRT1 widely plays a key role in cell survival and apoptosis, inflammatory stress adaptation to cell growth, differentiation, metabolism, and senescence, and prevents mitochondrial dysfunction through regulating its transcriptional activity and protein expression levels by changing the acetylation state of substrates (Jiao and Gong, 2020 ; Chelladurai et al, 2021 ; Lou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Silent information regulator 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD þ )-dependent deacetylase, regulates multiple cellular biological processes, including stress responses, cellular senescence, longevity, apoptosis, and inflammation [15,16]. Interestingly, SIRT1 has recently been identified as a novel therapeutic target for the prevention and treatment of several renal diseases [17][18][19]. Simultaneously, THC has been reported to alleviate diabetic cardiomyopathy mainly by attenuating oxidative stress and fibrosis via increasing the expression of SIRT1 [20].…”
Section: Introductionmentioning
confidence: 99%